Alanine tRNAs Translate Environment Into Behavior in Caenorhabditis elegans - Fernandes De Abreu, Diana Andrea; Salinas-Giegé, Thalia; Drouard, Laurence; Remy, Jean-Jacques (Frontiers in Cell and Developmental Biology, 2020)
Caenorhabditis elegans nematodes produce and maintain imprints of attractive chemosensory cues to which they are exposed early in life. Early odor-exposure increases adult chemo-attraction to the same cues. Imprinting is transiently or stably inherited, depending on the number of exposed generations. We show here that the Alanine tRNA (UGC) plays a central role in regulating C. elegans chemo-attraction. Naive worms fed on tRNAAla (UGC) purified from odor-experienced worms, acquire odor-specific imprints. Chemo-attractive responses require the tRNA-modifying Elongator complex sub-units 1 (elpc-1) and 3 (elpc-3) genes. elpc-3 deletions impair chemo-attraction, which is fully restored by wild-type tRNAAla (UGC) feeding. A stably inherited decrease of odor-specific responses ensues from early odor-exposition of elpc-1 deletion mutants. tRNAAla (UGC) may adopt various chemical forms to mediate the cross-talk between innately-programmed and environment-directed chemo-attractive behavior.